The potential biological effects of quercetin based on pharmacokinetics and multi-targeted mechanism in vivo. Issue 5 (4th May 2022) - Keranmu, Adili; Pan, Li-Bin; Yu, Hang; Fu, Jie; Liu, Yi-Fang; Amuti, Siyiti; Han, Pei; Ma, Shu-Rong; Xu, Hui; Zhang, Zheng-Wei; Chen, Dong; Yang, Fei-Ya; et al.
Abstract: Quercetin is a plant-derived polyphenol flavonoid that has been proven to be effective for many diseases. However, the mechanism and in vivo metabolism of quercetin remains to be clarified. It achieves a wide range of biological effects through various metabolites, gut microbiota and its metabolites, systemic mediators produced by inflammation and oxidation, as well as by multiple mechanisms. The all-round disease treatment of quercetin is achieved through the organic combination of multiple channels. Therefore, this article clarifies the metabolic process of quercetin in the body, and explores the new pattern of action of quercetin in the treatment of diseases. Graphical Abstract: UF0001